Estudo de características adaptativas à submersão de plantas jovens de ingá (Inga vera Willd.), virola (Virola surinamensis (Roland. ex Rottb.) Warb.) e seringueira (Hevea brasiliensis Muell. Arg.) - Botelho, Marcel do Nascimento (1996)
The aime of this work was to evaluete the behavior of some tree species at low oxigen avaibility médium, as to both morphological and anatomical modifications, such as formation of aerenchyma and lenticels, emission of adventious roots, number and size of stomates, epinasty and leaf abscision, modification in the nitrate reductase activity and amount of some macro and micro molecules related with this phenomenon. The experiment was conducted at the Biology Department at the Universidade Federal de Lavras, utilizing as plant material young rubber tree (Hevea brasiliensis Muell. Arg.), Inga (Inga vera Willd.) and virola (V/ro/a surinaensis (Rolland. ex Rottb.) Warb.). Three treatments were analysed: (T1) cultivation with no flooding; (T2) cultivation with flooding of the root system; (T3) cultivation with total flooding of the plant. Between the fifth and eighth days after induction of the treatment (DAIT), ali the plants cultivated with flooding of the root system and rubber trees with partial submersion of the aerial part showed an elargement of lenticels, lasting this way till the end of the experimental period (45 DAIT). From the 28 DAIT on inga plants under flooding of the root system, emission of adventicious roots became visible, which did not occur in any other treatment and species throughout the experimental period. At the end of the experimental period, anatomical evaluations were done on plants of inga and virola, not finding formation of aerenchymas, as well as significant alterations were not found in the structure of stem, root and mesophyll, and stomate number of these plants. There was a fall in nitrate reductase activity in the root and leaf of the plants under flooding of the root system and total flooding, showing that there was no nitrogen uptake in these species, in these experimental conditions. Total soluble sugars accumulation in the roots of the plants of inga and virola, denote that these species tolerated flooding becaue of the allocation and/or re-allocation of storages compounds which supported the root system. The break of the growth showed by inga and virola plants cultivated under total submersion, and by rubber trees cultivated with flooding of the root system and partial submertion of the aerial part, showed that according to the flooding level, these species dispose of different strategies to survive at the end of experiment.